IMPLEMENTAÇÃO DO MODELO TPM NUMA EMPRESA DO SETOR CERÂMICO - Tiago Figueiredo Teles Lopes (2021)
Maintenance plays a crucial role in the efficiency and durability of equipment. The implementation of a maintenance program that supports and reduces stoppages and damages that cause delays or failures in the level of service is essential to guarantee production flows and stability. From this need arises the Total Productive Maintenance model, implementing continuous improvement in maintenance, ensuring improved equipment conditions and reduced breakdowns/downtime. This work aims to apply the Total Productive Maintenance model in a process industry group in the ceramic sector, specifically focusing on one of the group's industrial units, following the project throughout the intervention schedule of the Kaizen Institute. The processes in this industry cause high wear to equipment, which translates into a high number of breakdowns and stoppages. These stops have a negative effect on the fulfillment of deliveries, namely when demand is high as in 2021 and stocks are relatively low. The project allowed to reduce the number and intervention times of the pilot equipment, thus increasing its OEE by 10% and the industrial unit's turnover by 3%, demonstrating the importance of continuing the Total Productive Maintenance in the other equipment of the industrial unit.